EVALUASI KINERJA POMPA PCP DAN IDENTIFIKASI KONDISI UNDERLOAD MENGGUNAKAN EFICIENCY VOLUMETRIC PADA VARIASI FREKUENSI OPERASI - Irsyad Afi Asyhari Putra; Hadziqul Abror (Universitas Jember, 2025)
The decline of reservoir pressure and the increase of water cut in mature oil fields often lead to a decrease in oilproduction, making wells uneconomical under natural flow conditions. Progressive Cavity Pump (PCP) is an artificiallift system commonly applied in such conditions due to its characteristics as a positive displacement pump. This studyaims to evaluate the performance of the existing PCP in Well X of Field Z and to identify underload conditions usingvolumetric efficiency as the main indicator. The analysis was conducted using secondary data through InflowPerformance Relationship (IPR) analysis with the Vogel method, nodal analysis, and evaluation of PCP performanceunder operating frequency variations ranging from 30 Hz to 60 Hz. The results show that Well X is producing atapproximately 90% of its maximum inflow capacity, indicating that reservoir inflow is the main limiting factor forproduction increase. Although increasing the operating frequency raises total fluid production, the volumetric efficiencydecreases from 85.3% at 30 Hz to 56.1% at 60 Hz, indicating underload conditions caused by the imbalance betweenpump capacity and reservoir inflow capability. The study concludes that the underload condition of the PCP is not dueto improper pump design but to limited reservoir inflow, and volumetric efficiency is an effective parameter for identifyingunderload in PCP operations.